Optimasi Co-processed Disintegrant Sodium Starch Glycolate dan Pati Kacang Merah (Phaseolus vulgaris L.) sebagai Bahan Penghancur Fast-Disintegrating Tablet Ondansetron Hydrochloride - Rina Suciati; Gunawan Setiyadi (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Ondansetron HCl is a drug that can block serotonin sites that cause nausea and vomiting. Ondansetron administered in fast disintegrating tablet preparations is expected to make it easier for patients to swallow it since it dissolves quickly with the help of saliva. Red bean starch has a moisture content of 9.14% and amylose content of 44.83±1.56% which is useful as a tablet crusher. Sodium starch glycolate (SSG) is a good disintegrant because it has a swelling ability of 300% in water. In this research, co-processed method is used which can reduce the water content and shorten the tablet crushing time effectively. The purpose of this study was to determine the effect of the different ratios of SSG with red bean starch in co-processed disintegrant on the physical properties of Ondansetron FDT, especially disintegration time, friability and dissolution of tablets and to determine the effect of using co-processed disintegrant SSG-red bean starch in the ondansetron FDT formula with formulas that use non-co-processed disintegrants. The optimization method used in this study was the simplex lattice design with components optimized being SSG and red bean starch in a ratio of 0.5:0.5 (FI), 0.75: 0.25 (FII), 0:1 (FIII), 0.25:0.75 (FIV), and 1:0 (FV). The responses used in the optimization were the physical properties of tablets in the form of friability, disintegration time and tablet dissolution. The optimum formula obtained from the experiment was a formula with a ratio of SSG and red bean starch 0.208:0.792. The predicted response of the optimum formula and the response of the verification formula were 0.61% and (0.66 ± 0.08) % friability, respectively, 37.98 seconds of disintegration and (39.90 ± 0.72) seconds and 97 dissolution 88% and (97.45 ± 0.66) %. The response of the verification formula was within the confidence interval of the prediction response, which indicates that the optimization produces a good prediction. The response of the optimum formula was then compared with the response of the same formula but containing a combination of non-co-processed SSG and red bean starch using a t test with a 95% confidence level. The results of the analysis showed that the P-value for friability was 0.1270.05 and dissolution was 0.0590.05, with no significant difference between the two. Meanwhile, the P-value for disintegration time was 0.006 0.05, which means that there was a significant difference between the co-processed and non-co-processed optimum formulas.Keywords: red bean starch, sodium starch glycolate, simplex lattice design, Ondansetron HCl and fast disintegrating tablet.